Work Environment, Spiritual, and Motivational Factors Affecting Job Satisfaction among Hospital Nurses: A Systematic Review - Ida Yanriatuti; Tan Nina Fibriola; Kornelis Nama Beni; Fitriyanti Patarru' (Jurnal Ners, 2019)
Introduction: Patient services at the hospital cannot be separated from the role of the nurse. Therefore, nurses must work professionally to provide better nursing care. There are several factors that can affect the performance of the nurses, one of which is job satisfaction. The purpose of a systematic review is to understand the factors that influence the job satisfaction of nurses in hospitals.Methods: For a systematic review, the search was focused on the PubMed, Science Direct and Scopus database literature with the keywords ‘job satisfaction’ and ‘nurses’. The search identified 15 relevant research articles from the 10,530 original articles that were full texts published between 2015 and 2018.Results: The results showed that the job satisfaction of the nurses was influenced by their leadership, work environment, career path, the relationship with their co-workers, salary, the relationship between the organizations, appreciation, communication, opportunity, organizational commitment, work schedule, work stress, empowerment and work rotation. The results also indicated that high job satisfaction leads to lowering nurse retention and burnout, in addition to an improved quality of patient care.Conclusion: The nurse’s job satisfaction needs to get serious attention from hospital management because it plays an important role in improving the health care service quality in the hospital.